An Analysis of Academic Libraries’ Participation in 21st Century Library Trends - Catalano, Amy Jo; Glasser, Sarah; Caniano, Lori; Caniano, William; Paretta, Lawrence (Evidence Based Library and Information Practice)

(untitled) (University of Alberta Library, 2018)
Objective – As academic libraries evolve to meet the changing needs of students in the digital age, the emphasis has shifted from the physical book collection to a suite of services incorporating innovations in teaching, technology, and social media, among others. Based on trends identified by the Association of College and Research Libraries (ACRL) and other sources, the authors investigated the extent to which academic libraries have adopted 21st century library trends.Methods – The authors examined the websites of 100 Association of Research Libraries (ARL) member libraries, their branches, and 160 randomly selected academic libraries to determine whether they adopted selected 21st century library trends.Results – Results indicated that ARL member libraries were significantly more likely to adopt these trends, quite possibly due to their larger size and larger budgets.Conclusion – This research can assist librarians, library directors, and other stakeholders in making the case for the adoption or avoidance of particular 21st century library trends, especially where considerable outlay of funds is necessary.